Supernumerary ovary on recto-sigmoid colon with associated endometriosis - Chul Kwon Lim; Hee Jin Kim; Joon Sook Pack; Joong Gyu Ha; Yun Seok Yang; Hye Kyung Lee; Seung Hyun Kim (Korean Society of Obstetrics and Gynecology, 2018)
A supernumerary ovary is a rare gynecological anomaly, and is usually excised due to its malignant transformation potential. We report a case of a supernumerary ovary and endometriosis situated on the anterior rectosigmoid colon. When laparoscopy was conducted, a firm, 5-cm mass was discovered on the anterior rectosigmoid colon along with normal ovaries. In this case, the discovery of a supernumerary ovary implied the presence of endometriosis. It is unusual for endometriosis and a supernumerary ovary to exist simultaneously.